2017
DOI: 10.1177/1352458517690270
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of modifiable risk factors in the progression of multiple sclerosis

Abstract: MS progression was consistently associated with low vitamin D levels, and smoking was associated with a more rapid decline in MS disability. Studies used a variety of methods, predictors, and outcomes making it difficult to draw conclusions. Future studies should focus on prospective assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(62 citation statements)
references
References 32 publications
1
61
0
Order By: Relevance
“…Numerous studies have examined risk factors for the development of multiple sclerosis (MS), 1 whereas more recently, long-term and population-based studies of factors affecting MS disability worsening have become feasible. 2 Studies have shown that male sex, progressive disease course at onset, and older age at onset are associated with disability worsening. [3][4][5] A paucity of evidence remains with regard to modifiable risk factors for MS disability worsening, but comorbid conditions are being increasingly explored as a potential avenue for intervention.…”
mentioning
confidence: 99%
“…Numerous studies have examined risk factors for the development of multiple sclerosis (MS), 1 whereas more recently, long-term and population-based studies of factors affecting MS disability worsening have become feasible. 2 Studies have shown that male sex, progressive disease course at onset, and older age at onset are associated with disability worsening. [3][4][5] A paucity of evidence remains with regard to modifiable risk factors for MS disability worsening, but comorbid conditions are being increasingly explored as a potential avenue for intervention.…”
mentioning
confidence: 99%
“…Therefore, factors affecting the health of PwMS play an important role in the life of the partner and the couple. Increasingly, there is evidence of associations between modification of lifestyle-related risk factors and improved mental and physical health outcomes in MS (D'Hooghe, Nagels, Bissay, & De Keyser, 2010;Fitzgerald et al, 2018;Hempel et al, 2017;Jelinek et al, 2016;Levin et al, 2014;Marck et al, 2014). PwMS who attended an intensive residential workshop regarding evidence-based lifestyle interventions reported improved HRQOL 5 years post-intervention (Hadgkiss, Jelinek, Weiland, Rumbold, et al, 2013;Li et al, 2010).…”
mentioning
confidence: 99%
“…Overall, 11 records were included in this review [100,[204][205][206][207][208][209][210][211][212][213] (Supplemental Figure S6). We focused on publications that examined the association between vitamin D and the development of MS or clinical activity of MS. Supplemental Tables S22-S24 provide information about the included studies and the assessed quality based on AMSTAR 2.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding clinical outcomes, eight publications that conducted SRs of mainly RCTs [204,205,207,[209][210][211][212][213] focused on changes in the expanded disability status scale (EDSS). In summary, the studies found no significant therapeutic effect of vitamin D on EDSS and/or concluded that vitamin D supplementation had no effects on EDSS.…”
Section: Therapeutic or Adjuvant Vitamin D Supplementation In Ms Patimentioning
confidence: 99%